Corporate Governance and Risk Management Information Disclosure in Malaysian Listed Banks: Panel Data Analysis - Sheila Nu Nu Htay, Hafiz Majdi Ab. Rashid (International Review of Business Research Paper, 2011)
Corporate governance issue has attracted the researchers, including the Malaysian researchers due to the 1997-1998 economic crises. Furthermore, it is undeniable that the banking sector is the heart of the economy in any country and it cannot be separated since it is the main source in mobilizing the monetary system. Thus, this study investigates the impact of corporate governance on risk management information disclosure of Malaysian listed banks by using a panel data analysis. Effectiveness and goodness a corporate governance structure is determined by the board leadership structure, board composition, board size, director ownership, institutional ownership and block ownership. The researcher develops risk management information disclosure index and conducts content analysis by cross checking between the risk management disclosure in the annual reports and the disclosure index. Accountants and financial analysts play the important role since the disclosure score used in this study is weighted disclosure score after considering their opinions because they are the group who represent preparers and users of the accounting information respectively. This research finds that higher proportion of independent directors and lower directors’ ownership lead to higher risk management information disclosure.